An Analysis of Traditional Cosmogony in African Languages Through Thomas Mofolo's Chaka and Andrew Ekwuru's Song of Steel - Richmond Jean-Baptiste Gnoleba MADOU (Akofena)
UNE ANALYSE DE LA COSMOGONIE TRADITIONNELLE DANS LES LANGUES AFRICAINES A TRAVERS LE CHAKA DE THOMAS MOFOLO ET LE SONG OF STEEL D'EKWURU